Profitability of Robusta Coffee (Coffea canephora L.) at farm level in Quirino, Philippines - Martinez, Juniora Blessie Ann N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research study was conducted to determine the profitability of the robusta coffee at farm level from the crop year 2015-2017 in Quirino province, the top two coffee-producing in Cagayan Valley. It specifically aimed to: describe the production and financial management practices of the coffee farmers, analyze the profitability of coffee crop production, identify gaps/constraints encountered by the farmers, and determine innovative solutions to enhance the coffee industry. Three producing municipalities namely, Aglipay, Diffun, and Maddela were selected purposively for the study. Primary data were collected from the coffee farmers and key informants. Secondary data were also obtained from various government and private agencies. The study used a descriptive research method with a structured survey questionnaire as the primary research tool. The study revealed that the average net profit margin in the farmer’s level from the crop year 2015-2017 was 63.21% which was lower than the industry standard. The problems and constraints identified were: the high cost of farm inputs, climate change, inadequate post-harvest facilities, and limited transportation facilities. This resulted in loss of crops, limited access to the market, and high transportation costs. The study recommends that the support and assistance from the local government and national agencies such as capacity building, technology transfer, and shared service facilities will help improve the profitability of coffee.